2017
DOI: 10.3389/fnagi.2017.00221
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Latin America: Epidemiological Evidence and Implications for Public Policy

Abstract: Population aging is among the most important global transformations. Today, 12% of the world population is of age 60 and over and by the middle of this century this segment will represent 21.5%. The increase in population of those aged 80 and over, also referred to as the “oldest old” or the “very elderly”, will be even more pronounced, going from 1.7% of the population to 4.5% within the same period. Compared to European and North American countries, Latin America (LA) is experiencing this unprecedented demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
0
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 124 publications
(157 citation statements)
references
References 80 publications
4
129
0
24
Order By: Relevance
“…The impact of educational level in cognitive performance can be understood in terms of how it promotes the development of different abilities in the brain and also on how it contributes for the development of “cognitive reserve,” a concept that proposes that individual differences in cognitive processing lead to different degrees of resilience in face of brain pathology . In developing countries, such as Brazil, schooling years vary greatly among different regions, and a significant proportion of the elderly have low educational level . To address this problem, we created 2 versions of the CAMCog‐Short, one aiming individuals with 0 to 8 years of education, and another for subjects with >8 or more years of education.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The impact of educational level in cognitive performance can be understood in terms of how it promotes the development of different abilities in the brain and also on how it contributes for the development of “cognitive reserve,” a concept that proposes that individual differences in cognitive processing lead to different degrees of resilience in face of brain pathology . In developing countries, such as Brazil, schooling years vary greatly among different regions, and a significant proportion of the elderly have low educational level . To address this problem, we created 2 versions of the CAMCog‐Short, one aiming individuals with 0 to 8 years of education, and another for subjects with >8 or more years of education.…”
Section: Discussionmentioning
confidence: 98%
“…In Brazil, a translated and adapted version of the CAMCog was published in 1999. Experience has shown that even though the CAMCog is suitable for diagnostic approach and follow‐up in the Brazilian population, it has some limitations, namely, the long time for administration and its susceptibility to the influence of educational level, a still important issue in developing countries …”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, dementia disability burden in Latin America has grown more than have other health conditions in the last decades. 3 Thus, at the family level, dementia care will place a great burden on relatives, impacting the health of informal family caregivers. 3 Thus, at the family level, dementia care will place a great burden on relatives, impacting the health of informal family caregivers.…”
mentioning
confidence: 99%
“…3 Thus, at the family level, dementia care will place a great burden on relatives, impacting the health of informal family caregivers. 3,10,11 In fact, in these countries, the directly attributable cost of dementia exceeds that of depression, hypertension, diabetes, ischemic heart disease, and stroke. 3,10,11 In fact, in these countries, the directly attributable cost of dementia exceeds that of depression, hypertension, diabetes, ischemic heart disease, and stroke.…”
mentioning
confidence: 99%
“…Today, 12 % of the world's population is 60 years of age and older, and by the middle of this century, this segment will rise to 22 %. . This goes along with serious health concerns, as some of the most prevalent diseases are age‐related.…”
mentioning
confidence: 99%